Restricting Bunk Space Allotments to 6 or 10 Inches has Minimal Impact on Growth Performance in Limit-Fed Receiving Cattle - W. Cole Ellis; Zachary M. Duncan; Madeline S. Grant; William R. Hollenbeck; Evan C. Titgemeyer; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2024)
Objective:The objective of our experiment was to determine if bunk allotments of 6, 10, 14, or 18 in per head in pens containing 18 to 28 head impacts growth performance of growing calves limit-fed a high-energy dietbased on corn and corn co-products. Study Description:A total of 332 crossbred heifers were blocked by source, stratified by individual arrival weight, and assigned to a pen. Pens were randomly assigned to one of four treatments: 6, 10, 14, and 18 in of bunk space per head. Pens contained 18 to 28 head per pen. Heifers were limit-fed once daily at 2.0% of body weight (BW) [dry matter (DM) basis] for a 56-day period. Results:Final BW and average daily gains (ADG) following the 56-day period did not differ (P≥ 0.20) among treatments. The standard deviation of ADG responded quadratically (P= 0.05) where variation in weight gain was greater in calves allotted 14 in of bunk compared with calves allotted 6, 10, or 18 in of bunk. The Bottom Line:Bunk allotments as low as 6 in per head did not reduce the growth performance of limit-fed growing cattle during a 56-day receiving period.
Keywords: bunk space; limit-feeding; growing cattle